2013
DOI: 10.6007/ijarbss/v3-i7/8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clustering and Collaboration on Product Innovativeness: The Case of Manufacturing Small and Medium Enterprises (SMEs) in Kenya

Abstract: The study aimed at determining the effect of clustering and collaboration on product innovativeness (PI) in the context of manufacturing SMEs in Kisumu, Kenya. To answer the questions this empirical study raised, a sample of 126 SMEs on the basis of the manufacturing hubs of Kisumu, Kenya. This study provided evidence in support of clustering and collaboration on product innovativeness. Further research is needed to confirm and extend the present results by replicating the principal features of this study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
2
5
0
1
Order By: Relevance
“…The study further showed that 76 (50%) respondents strongly agreed that MFIs have created more competitive products, 68(45%) respondents agreed with, while 7(5%) respondents were not sure whether the competitive products would enhance growth of MFLs. These findings are in agreement with findings of Ringera and Muturi (2019) that it is fundamental for MFIs to constantly engage in providing new differentiated products that fulfill customer needs (Gudda et al, 2013) are in agreement with the study that differentiated products will enhance MFIs competiveness and growth.. Finally, 60(40%) of respondents agreed that adoption of new innovative products Contribute to growth of MFIs, while 91(60%), strongly agreed on adaption of new innovative products.…”
Section: Product Innovation On Growth Of Mfissupporting
confidence: 90%
“…The study further showed that 76 (50%) respondents strongly agreed that MFIs have created more competitive products, 68(45%) respondents agreed with, while 7(5%) respondents were not sure whether the competitive products would enhance growth of MFLs. These findings are in agreement with findings of Ringera and Muturi (2019) that it is fundamental for MFIs to constantly engage in providing new differentiated products that fulfill customer needs (Gudda et al, 2013) are in agreement with the study that differentiated products will enhance MFIs competiveness and growth.. Finally, 60(40%) of respondents agreed that adoption of new innovative products Contribute to growth of MFIs, while 91(60%), strongly agreed on adaption of new innovative products.…”
Section: Product Innovation On Growth Of Mfissupporting
confidence: 90%
“…Inovasi didefinisikan sebagai kemampuan perusahaan untuk mempertahankan ide-ide baru yang dapat diinterpretasikan menjadi produk, jasa, teknologi, atau pasar baru (Gudda, Bwisa & Kihoro, 2014). Innovation-oriented merupakan kecenderungan pelaku bisnis mencari ide-ide pemasaran yang baru baik dari dalam perusahaan maupun dari aktivitas eksternal perusahaan (Fiore et al, 2013).…”
Section: Pengaruh Innovation-oriented Terhadap Kesuksesan Bisnisunclassified
“…Its justification was high research and development costs in an environment whereby technology is ever converging as well as the need to harmonize technological standards (Gnyawali and Park, 2009). Other factors included strategic alliances and networking which have similarly and separately been shown to have an effect on innovativeness (Mothe and Link, 2002;Gudda et al, 2013;Osei et al, 2016). The causal effect of strategic alliances and networking has not been well researched.…”
Section: The Impact Of Environmental Dynamismmentioning
confidence: 99%